ANALISIS PRODUKTIVITAS DAN STABILITAS BAWANG MERAH DI KABUPATEN BANTUL (ANALYSIS ON SHALLOTS PRODUCTIVITY AND STABILITY IN BANTUL DISTRICT) - Rajiman, Rajiman (Jurnal Ilmu-Ilmu Pertanian, 2013)
This study aimed to design development commodities the shallot in an effort to improve its productivity and stability. Research carried out on August October 2009, in Bantul District. Data analysis methods used Magic Box Methods. The principle of the magic box by using the parameters of the productivity and stability. Productivity data of shallot which used the rayon in 2004 2008. The results showed the productivity (PR) of shallot in Bantul District, categorized as low if the productivity of <76,7 kw / ha, moderate (76,7 ≤ PR<127,86 kw / ha) and high if the PR ≥ 127,8 kw/ha. Stability categorized low if the value CV> 20%, moderate (10-20%) and high if <10%. Results of analysis showed that the magic box at Sanden Rayon has the same stability and productivity, ie productivity of medium and high stability (Box 4. The rayon of Srandakan, Kretek, Pundong and Pandak has productivity and stability are being (Box 5). The Rayon of Imogiri and Bambanglipuro has productivity of medium and low stability (Box 6). Based on the analysis of a magic box, empowerment is done through two approaches according to the resulting box. In general empowerment activities with research and extension. Empowerment of Box 4 include: 1) the increased of land fertilizer 2). the use of variety. Empowerment of box 5 and 6 include : 1) the increased of land fertilizer 2). the use of variety and 3) manajeman of cultivation.